An Evaluation of Logistic Management of Vaccines in Anand District - Patel, Tushar A; Patel, Rakesh M (National Journal of Community Medicine, 2013)
Background: To achieve good vaccination coverage it is essential that vaccines are supplied in appropriate quantity at appropriate time. This demands evaluation of logistic management of vaccines. The objectives of the study were to assess management of vaccine logistic at PHC and Sub-centre level and to identify weaknesses in the processes of acquisition, storage, distribution and utilization of vaccines. Method: An observational study was conducted among PHCs of Anand District, Gujarat. Data from 20 PHCs was collected with pre tested questionnaire mainly from vaccine stock register. Data included Date and amount of vaccine delivery, Opening balance on the day of receipt and closing balance after receipt. Results: Nearly three-fourths of time (72%) OPV was received below minimum level. More than one third (40%) and nearly half (46%) of vaccine deliveries of DPT and Hepatitis B took place below minimum level. Significant proportion of vaccine deliveries resulted in excess stock with number for measles (96%) and BCG (84%) being highest. OPV (average 18 days) and BCG (average 27 days) were most likely vaccines to go out of stock. Duration of stock outs for these vaccines was also longer. Observed rates of wastage for all vaccines exceeded estimated wastage of 25%. Nearly one third of sessions were conducted without measles (33%) and OPV (29%). OPV, BCG and Measles had wastage rate of 46%, 45% and 40% respectively. Conclusion: Delayed placement of the orders and inequitable distribution both are contributing to unavailability of vaccines. To avoid shortage of the vaccines it is essential that either wastage is reduced by reducing number of dose per vial or wastage factor increased at the time of calculation of requirement.